Non-inferiority of mammalian cell-derived quadrivalent subunit influenza virus vaccines compared to trivalent subunit influenza virus vaccines in healthy children: a phase III randomized, multicenter, double-blind clinical trial - Hartvickson, Robyn; Cruz, Marilou; Ervin, John; Brandon, Donald; Forleo-Neto, Eduardo; Dagnew, Alemnew F.; Chandra, Richa; Lindert, Kelly; Mateen, Ahmed Abdul (International journal of infectious diseases, 2015)
•The quadrivalent influenza vaccine (QIVc) demonstrated a similar safety profile and immune responses against all four vaccine strains without signs of immune interference on addition of an alternative lineage B strain.•QIVc met the non-inferiority criteria against all four vaccine strains.•Superiority for both influenza B strains over the unmatched B lineage was demonstrated.•No vaccine-related serious adverse events or deaths occurred.•QIVc offers promise as a vaccine with broader protection against both influenza B lineages in children ≥4 to <18 years of age when compared with current trivalent vaccines. The safety and immunogenicity of mammalian cell-derived quadrivalent influenza vaccine (QIVc) as compared with trivalent influenza vaccines (TIV1c/TIV2c) was evaluated in children aged ≥4 to <18 years. Two thousand three hundred and thirty-three subjects were randomized 2:1:1 to receive either one or two doses of study vaccine depending on previous vaccination status. Hemagglutination inhibition antibody responses for all four influenza strains were performed 3 weeks after the last dose. Reactogenicity and safety were also assessed (ClinicalTrials.gov: NCT01992107). QIVc met the non-inferiority criteria against all four vaccine strains and demonstrated superiority for both influenza B strains over the unmatched B lineage included in the comparator vaccines, when geometric mean titers and seroconversion rates were compared at 3 weeks after the last vaccination. Similar percentages of subjects experienced solicited and unsolicited adverse events (AEs) across all subgroups. Unsolicited AEs, serious AEs, medically attended AEs, and new onset chronic disease were reported in comparable percentages of subjects in all study groups. No vaccine-related serious AEs or deaths occurred. QIVc demonstrated a similar safety profile and immunogenicity responses against all four vaccine strains without signs of immune interference on addition of an alternate lineage B strain compared with TIV1c/TIV2c and may provide broader protection against both influenza B lineages in children.